Regulation of hepatocyte growth factor activator inhibitor 2 by hypoxia in breast cancer - Generali, D; Fox, S; Berruti, A; Moore, J; Brizzi, M; Patel, N; Allevi, G; Bonardi, S; Aguggini, S; Bersiga, A; Campo, L; Dogliotti, L; et al. (2007)
Purpose: To examine the in vitro regulation of hepatocyte growth factor activator inhibitor type 2 (HAI-2) in breast cancer cells and the in vivo predictive role for the efficacy of chemoendocrine primary therapy in patients with breast cancer. Materials and Methods: HAI-2 regulation was studied in a panel of breast cancer cell lines comparing normoxia to hypoxia. The effect of HIF-1α RNAi on HAI-2 expression was evaluated in these cells. HAI-2 was examined in breast cancer using in situ hybridization and immunohistochemistry. The HAI-2 predictive role was assessed in T2-4 N0-1 breast cancers (n = 177) enrolled in a neoadjuvant randomized trial comparing epirubicin versus epirubicin + tamoxifen. Results: HAI-2 mRNA and protein were regulated by hypoxia in the c-erbB2- positive cell lines, SKBR3 and BT474, and controlled by HIF-1α in these cells. Immunohistochemistry confirmed this profile with high expression of HAI-2 in c-erbB2-positive breast cancer. HAI-2 was correlated with T status (P < 0.004), node involvement (P = 0.01), and c-erbB2 expression (P = 0.05). HAI-2 also correlated with hypoxia markers such as carbonic anhydrase IX expression (P = 0.01) and HIF-1α Additionally, high levels of HAI-2 were a significant predictor for poor clinical complete response to preoperative epirubicin in univariate (P = 0.01) and multivariate analyses (P = 0.016). No correlation with disease-free survival and survival was observed. Conclusion: HAI-2 expression in breast cancer correlated with tumor aggressiveness in vivo. It is a HIF target in c-erbB2- positive cells and it is an independent negative predictive factor of efficacy of anthracycline therapy. The interaction of HAI-2 with the hepatocyte growth factor activation pathway may be a useful site for therapeutic intervention. © 2007 American Association for Cancer Research.